Faktor – Faktor Yang Mempengaruhi Kecemasan Pada Ibu Hamil Resiko Tinggi - Rozikin, Moch Fahrur; Martini, Diah Eko; Ekawati, Heny (Jurnal Keperawatan Muhammadiyah, 2025)
Anxiety during pregnancy is a common psychological condition, especially among high-risk pregnant women. Excessive anxiety may negatively impact both maternal and fetal health. This study aimed to examine the relationship between maternal age, parity, and social support with anxiety levels in high-risk pregnant women at RS Arsy Paciran. A correlational analytic study with a cross-sectional approach was conducted on 35 respondents selected using consecutive sampling. Anxiety levels were measured using the DASS-42 questionnaire, and social support was assessed using the Maternity Social Support Scale (MSSS). Data were analyzed using the Spearman Rank correlation test. The results revealed that maternal age (p=0.022), parity (p=0.009), and social support (p=0.001) had significant correlations with anxiety levels. Women who were younger or older than the ideal reproductive age range, had higher parity, or received low levels of social support experienced greater anxiety. Among the three variables, social support showed the strongest negative correlation with anxiety (rs = -0.615). This study concludes that maternal age, parity, and social support are dominant factors influencing anxiety in high-risk pregnancies. Healthcare professionals are encouraged to provide targeted education and consistent support to pregnant women, particularly those identified as high risk, to promote mental well-being during pregnancy.